The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.3928/01477447-20120822-17
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Less-invasive Surgical Technique on Cement Mantle Quality in Total Knee Arthroplasty

Abstract: The purpose of this study was to assess the effects of a less-invasive midvastus exposure during total knee arthroplasty (TKA) on cement mantle grade compared with a standard parapatellar arthrotomy and standard TKA. Fifty consecutive cemented minimally invasive TKAs using a midvastus approach, patellar subluxation without eversion, and less-invasive instrumentation were compared radiographically with a control cohort of 50 consecutive cemented standard TKAs. To eliminate patient selection bias, the standard c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Minimally invasive TKA through the mid-vastus approach has reported to compromise the quality of the femoral cement Table 2 Cement void in different zones of the femoral, tibial, and patellar components in the conventional and computer-assisted minimally invasive total knee arthroplasty (TKA) group mantle and result in a higher rate of tibial cement debris. 17 However, one study reported no progressive radiolucency 6 months after minimally invasive or conventional TKA. 18 In our study, the only variable affecting the quality of cementation was the amount of exposure where minimally invasive TKA resulted in a wider cement void beneath the anterior flange of the femoral component and a higher rate of retained cement in the posterior or lateral aspects of the tibial component.…”
Section: Discussionmentioning
confidence: 99%
“…Minimally invasive TKA through the mid-vastus approach has reported to compromise the quality of the femoral cement Table 2 Cement void in different zones of the femoral, tibial, and patellar components in the conventional and computer-assisted minimally invasive total knee arthroplasty (TKA) group mantle and result in a higher rate of tibial cement debris. 17 However, one study reported no progressive radiolucency 6 months after minimally invasive or conventional TKA. 18 In our study, the only variable affecting the quality of cementation was the amount of exposure where minimally invasive TKA resulted in a wider cement void beneath the anterior flange of the femoral component and a higher rate of retained cement in the posterior or lateral aspects of the tibial component.…”
Section: Discussionmentioning
confidence: 99%